Alpha-Synuclein Physiology and Pathology: A Perspective on Cellular Structures and Organelles - Bernal-Conde, Luis D.; Ramos-Acevedo, Rodrigo; Reyes-Hernández, Mario A.; Balbuena-Olvera, Andrea J.; Morales-Moreno, Ishbelt D.; Argüero-Sánchez, Rubén; Schüle, Birgitt; Guerra-Crespo, Magdalena (Frontiers in Neuroscience, 2020)
Alpha-synuclein (α-syn) is localized in cellular organelles of most neurons, but many of its physiological functions are only partially understood. α-syn accumulation is associated with Parkinson’s disease, dementia with Lewy bodies and multiple system atrophy as well as others synucleinopathies, however, the exact pathomechanisms that underlie these neurodegenerative diseases remain elusive. In this review, we describe what is known about α-syn function and pathophysiological changes in different cellular structures and organelles, including what is known about its behavior as a prion-like protein. We summarize current knowledge of α-syn and its pathological forms, covering its effect on each organelle, including aggregation and toxicity in different model systems, with special interest on the mitochondria due to its relevance during the apoptotic process of dopaminergic neurons. Moreover, we explore the effect that α-syn exert by interacting with chromatin remodeling proteins that add or remove histone marks, upregulates its own expression and resume the impairment that α-syn induce in vesicular traffic by interacting with the endoplasmic reticulum. We then recapitulate the events that lead to Golgi apparatus fragmentation, caused by the presence of α-syn. Finally, we report the recent findings about the accumulation of α-syn, indirectly produced by the endolysosomal system. In conclusion, many important steps into the understanding of α-syn have been made using in vivo and in vitro models, however, the time is right to start integrating observational studies with mechanistic models of α-syn interactions, in order to look at a more complete picture of the pathophysiological processes underlying α-synucleinopathies.